Augmented Reality and Animation Supported-STEM Activities in Grades K-12: Water Treatment - Necla Dönmez Usta; Neslihan Ültay (Journal of Science Learning, 2022)
Animation is used to increase the interest and engagement of students in the learning environment. Animation is exciting and fun, and using animation, abstract concepts are easy to present, display, and convey to students. Augmented reality, like animation, can help make it easier to understand abstract concepts. In many areas, augmented reality is used in education since it perfectly integrates virtual content with the natural world. STEM education is one of the areas where augmented reality can be used effectively. In this context, this research aimed to reveal the fourth-grade students' opinions about augmented reality and animation-supported STEM activities on the "Water Treatment" topic. These  STEM activities were carried out with 15 (7 females, 8 males) fourth-grade students from a primary school in Turkey and lasted for 6 lesson hours. This study is a case study. As data collection tools in the study, the Know-Want-Learned chart, and the Application General Evaluation Form, which consists of eight open-ended questions developed by the researchers, were used. Based on the study's findings and the researchers' observations, it was determined that the augmented reality and animation-supported STEM activities are appropriate for acquisition, content, application, active participation, duration, and student level. In addition, the activities were enjoyable, humorous, engaging, and exciting. It is recommended in this context to conduct similar studies on different disciplines or concepts.